Postdischarge Opioid Prescription after Cesarean: A Quality Improvement Initiative - Pellino, Katherine T.; Kershner, Alexandra; Peterson, Erika L. (American Journal of Perinatology, 2023)
Objective This study aims to determine if adoption of a user-friendly algorithm for individualized opioid prescribing at discharge would decrease the number of opioids prescribed after cesarean delivery.Study Design As part of a quality initiative, we developed and implemented an algorithm for opioid prescribing at discharge for patients after cesarean delivery. The intervention group comprised patients delivering by cesarean in the 6 months following initiation of the intervention. The intervention group was divided into three groups based on inpatient opioid needs 24 to 48 hours after delivery. Oxycodone tablets were prescribed at discharge based on inpatient group. The control group comprised patients delivering at the same institution in the 6 months prior to initiation of the intervention. The primary outcome was number of oxycodone tablets prescribed at discharge. The secondary outcome was the proportion of patients with a pain-related encounter or additional oxycodone prescription up to 6 weeks after delivery.Results From July to December 2020, a total of 382 subjects met criteria for the intervention. The comparison group consisted of 391 subjects discharged from January to June 30, 2020, after cesarean. Baseline characteristics and inpatient opioid use 24 to 48 hours after delivery did not differ between the groups. Compared with the control group, subjects in the intervention group had fewer oxycodone tablets prescribed at discharge (11.1 vs. 15.8, p < 0.001). The number of pain-related encounters within 6 weeks of delivery did not differ between the intervention and comparison groups (10.5 vs. 10.3%, p = 0.82). There was no increase in the additional number of oxycodone prescriptions after discharge (4.7% in the intervention group vs. 4.3% in the control group, p = 0.81).Conclusion Discharge opioid prescribing based on inpatient use after cesarean reduces the number of opioids prescribed without increasing the number of pain-related encounters after discharge. A simple algorithm may ensure compliance from prescribers.Key Points
Keywords: cesarean delivery; cohort; enhanced recovery; opioid prescribing; opioids; quality improvement